Checklist and comments on the jumping plant-lice (Hemiptera: Psylloidea) from Brazil - Burckhardt, Daniel; de Queiroz, Dalva Luiz (Zootaxa, 2012)
The published records of jumping plant-lice from Brazil comprise 70 named species but four are erroneous or doubtful. For one species a variety has been described with uncertain status. Seven named species records are added here based on recent collections bringing the number of valid species to 73. Four new combinations are proposed: Colophorina favis (Brown & Hodkinson) (from Euphalerus), Euryconus fossiconis (Brown & Hodkinson) (from Euphalerus), Leuronota solani (Rübsaamen) (from Bactericera) and Macrocorsa beeryi (Caldwell) (from Psyllia). Additional unidentified species are recorded from the genera Auchmeriniella, Calophya, Ciriacremum, Euryconus, Isogonoceraia, Leuronota, Mastigimas, Pseudophacopteron and Livia, the last being considered a misidentification. Another 23 records concern psyllid galls which could not be attributed to any genus. The collection of psyllid galls from Brazil described by E. H. Rübsaamen was revised. The checklist provides for each species the general and Brazilian distributions as well as the host plants. Biogeographical and host plant patterns are briefly discussed. Half of the native psyllid genera are endemic to the Neotropic Region and slightly less than a third are restricted to the New World. Ten species are introduced from Australia (4), Europe (2), Asia (1) and other parts of South America (3). Fabaceae are host plants of a majority of members of the Psyllidae, whereas many Triozidae are associated with Myrtaceae.